O impacto organizacional e social das tecnologias emergentes: o caso das blockchains - Ferreira da Silva, C.; Cunha, P.; Melo, P. (Sistemas de informação: diagnósticos e prospetivas, 2022)
The results of a questionnaire that seeks to ascertain the organizational and social impact of the blockchain technology in Portugal are presented. It is structured according to the model proposed by the authors, which presents the following 3 parts: characterization of the respondents' profile, factors of knowledge and of use of the blockchain technology, and expectations and impact of this technology in Portugal. The main results indicate a still very low penetration in our country, as well as pressing needs for dissemination, investment, education and training on this technology. The relevance of the results presented in this chapter is related to the importance of arousing interest, dissemination about the expected impact and measures to enhance the positive impact of this technology.